Vertical integration, collusion, and tariffs - Pedro Mendi; Rafael Moner-Colonques; José J. Sempere-Monerris (SERIEs - Journal of the Spanish Economic Association, 2011)
This article presents a link between tariff rates and industry structure in a dynamic setting. We examine the role of tariffs on final-goods in a firm's decision to integrate and collude in the presence of competitive imports. It is shown that, under some conditions, the upstream firm has an incentive to engage in vertical integration to introduce profitably a wholesale price above the world input price while not inducing any intermediate or final good imports. Higher tariffs downstream, even with no tariff protection upstream, make this strategy more profitable, and provide a rationale for a positive relationship between tariff protection and vertical integration, which is observed in some industries.
Keywords: F12; L12; L42; 330; vertical integration; Monopoly; tariffs; Vertikale Konzentration; Preiswettbewerb; Zollpolitik; Monopolistischer Wettbewerb; Theorie